1981
DOI: 10.1161/01.str.12.5.653
|View full text |Cite
|
Sign up to set email alerts
|

Microangioarchitecture of rat parietal cortex with special reference to vascular "sphincters". Scanning electron microscopic and dark field microscopic study.

Abstract: SUMMARY Microangioarchitecture of the rat parietal cortex was studied by means of scanning electron microscopy and dark field microscopy. The richest supply of blood vessels in the parietal cortex was found in layer HI + IV and layer V, where 2 isolated plexuses of microressels were prominent. Tbe appearance of the plexuses was quite different between motor and sensory areas. In the motor area the capillary plexuses were narrow and compact, while in sensory area the plexuses were wide and diffuse.Characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 17 publications
2
22
1
1
Order By: Relevance
“…On arteriolar branches of the infundibular and neural-lobe arteries, we found circular constrictions indicating the sites of structures capable of regulating blood flow toward the median eminence and neural lobe. Similar structures have been described at branching sites of cast arterioles in the rat parietal cortex (NAKAI et al, 1981). Conspicuous deep constrictions, caused by intra-arterial cushions at these sites, have also been noted at the origin of the hypophyseal arteries in the rat (MURAKAMI et al, 1993).…”
Section: Median Eminencesupporting
confidence: 68%
“…On arteriolar branches of the infundibular and neural-lobe arteries, we found circular constrictions indicating the sites of structures capable of regulating blood flow toward the median eminence and neural lobe. Similar structures have been described at branching sites of cast arterioles in the rat parietal cortex (NAKAI et al, 1981). Conspicuous deep constrictions, caused by intra-arterial cushions at these sites, have also been noted at the origin of the hypophyseal arteries in the rat (MURAKAMI et al, 1993).…”
Section: Median Eminencesupporting
confidence: 68%
“…Peppiatt et al (2006) revealed that this portion (capillary junction) is rich in pericytes. The term precapillary sphincter has been used to imply the functional significance of the area; that is, a region of varied lengths, up to 100 mm or more, which controls blood flow to the capillary bed under physiological conditions (Nakai et al, 1981). Whether ECs on the precapillary arterioles have an essential role in the mechanisms controlling the precapillary sphincter has never been evaluated in vivo.…”
Section: Endothelial Cellsmentioning
confidence: 99%
“…Of the three types of penetrating arteries reported, 19 we focused on relatively large penetrating arteries that travel to deep cortical layers, to measure precisely the diameter of the arteries, and to analyze the depth dependence of diameter changes. It was shown that small diameter arteries had a territory of only the upper layer cortex.…”
Section: Acquisition and Analysis Of The Time Course Of Changes In Armentioning
confidence: 99%
“…It was shown that small diameter arteries had a territory of only the upper layer cortex. 19 A total of six penetrating arteries from five animals were used for analysis of the time course of response to the NBM stimulation by cross-sectional imaging 20 at each cortical depth, including the cortical surface, in a 50-mm step. A train of 500 electrical pulses (50 Hz for 10 seconds) were repeated with an interval of 1 minute, according to a previous result showing that increased blood flow after 10-second stimulation of the NBM returns to control level within 20 to 30 seconds after the end of stimulation.…”
Section: Acquisition and Analysis Of The Time Course Of Changes In Armentioning
confidence: 99%